Papilla preservation flaps for periodontal regeneration of molars severely compromised by combined furcation and intrabony defects: Retrospective analysis of a registry‐based cohort. Issue 2 (23rd August 2019) - Cortellini, Pierpaolo; Cortellini, Simone; Tonetti, Maurizio S.
Abstract: Background: Furcation involvement and attachment loss are major predictors of tooth loss. The aim of this study was to describe specific designs for papilla preservation flaps (PPFs) and minimally invasive surgery to be used in compromised molars and report proof‐of‐principle data with 3 to 16‐year follow‐up in severely compromised molars due to the presence of combined furcation and intrabony defects. Methods: Forty‐nine subjects with furcated molars and deep intrabony defects were treated with PPFs, application of periodontal regenerative devices. Improvement as a consequence of therapy was defined as tooth retention, reduction in horizontal and vertical furcation involvement, decrease in probing depths, and increases in clinical attachment level. Subjects were maintained with regular supportive periodontal care. Results: At 1 year, 100% of maxillary and 92% of mandibular molars showed improvements. Improvements were not observed in molars with baseline hypermobility: two mandibular molars with hypermobility were extracted at the 1‐year follow‐up. Improvement in vertical sub‐classification was observed in 87.5% of maxillary and in 84.6% of mandibular molars. One‐year improvements could be maintained over the 3 to 16‐year follow‐up. Conclusions: PPFs and periodontal regeneration can be applied and provide clinical benefits to severely compromised molars due to the combined presence of furcation involvement and deep intrabony defects. These results were obtained in cases with an interdental peak of bone and gingival margin coronal to the furcation entrance in well‐maintained and compliant subjects. Randomized controlled clinical trials with medium‐ to long‐term follow‐up are needed to confirm these findings.